PENDIDIKAN MASYARAKAT SUKU ASLI (STUDI KASUS DUSUN SEJAHTERA DESA KEMBUNG BARU KECAMATAN BANTAN KABUPATEN BENGKALIS PROVINSI RIAU) - Desi Fitriana; Mita Rosaliza (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Tribal society belongs to a remote indigenous komonitas in Riau Province. One of them is located in the hamlet of Prosperous villages of Bloated New Sub Regency of Bengkalis Bantan. Quality of people's lives is still very low. This is evidenced by the number of low income communities as well as the level of education also is still low. The level of education of the natives is still very low, and much of the original tribe of children dropping out of school in the school age kejenjang legitimate continuing education as well as higher. This is because of the low level of family economics and lack of facilities and infrastructure that supports the development of the educational aspect in this village. The prosperous village has road access and do not have public transportation as a means of penujang. The meaning of education for tribal people of